Women inspiring women in STEM professional careers: Journeys from Latin America (LACCEI, 2024)
Achieving gender equality and empowering women and girls around the world is one of the Sustainable Development Goals (SDG) defined by the United Nations. Women are underrepresented in leadership roles at a professional level. Within the engineering and sciences sectors, the gender gap is notorious. There are several initiatives working towards promoting STEM vocations and inspiring women to pursue a professional career in STEM. The Matilda Latin American Open Chair is an academic space that brings people together to promote the participation of women in STEM careers, grow their skills, retain them, and help them to reach their full potential. The Matilda Chair is a collaboration of persons and institutions in Latin America. This work analyzes the fourth book titled “Matilda and Women in Engineering in Latin America 4” which integrates the journeys, stories, and experience from women in STEM to encourage other women to pursue careers in STEM, to further promote gender equality and diversity in these areas. The study analyzes the authors´ profile to understand their context and motivation to be part of the book and suggest strategies to hopefully engage more women in this effort. This work also analyzes the main messages given in each article of the book to understand what is relevant for women, the main challenges they have faced along the way and what advice and learning they share with the readers. Integrating these valuable experiences, their advice, and reflections, elevates the voice of women engineers to give them more visibility and inspire other women to follow their path.